Field reports, Sue Spieker, fall 1989 - Spieker, Susanet al (1989)
Field reports form by Sue Spieker with a contributor Linda Packard and a letter from Sue Spieker to Carl Bendorf about the sightings for fall 1989. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1989. Epson - sheet feed/flatbed